Dizionario gramsciano / Gramsci dictionary: Hegemony - Cospito, Giuseppe (International Gramsci Journal, 2023)
Hegemony is by now the most widely used concept of all those found in the Prison Notebooks and developed there by Gramsci. The first use in the Notebooks occurs very early on, purely in the sense of a political hegemony exercised by the so-called “Moderates” in the Risorgimento. There is no unique meaning attached to “hegemony” but an oscillation between a narrow “leadership” as contrasted with “domination” and a broader one which includes both “leadership” and “domination”, leading the allied classes or groups and dominating the opposing ones: in Gramsci’s words, the “ ‘normal’ exercise of hegemony” is characterized by a “combination of force and consent”. Hegemony is exercised across a variety of fields – not solely political as in the first use of the term, but “political-intellectual”, “intellectual, moral and political”, “politico-cultural” and “cultural”. And the content of political hegemony “must be predominantly of an economic order”. The intellectuals, as defined and discussed by Gramsci in the Notebooks, occupy a particular role in the exercise of hegemony in society by the dominant group and in the domination over society embodied by the State. In a struggle for hegemony, a subaltern group must go beyond the economic-corporative phase, to advance to “political-intellectual hegemony in civil society and become dominant in political society”. Hegemony is intimately connected with democracy, such that in a hegemonic system “there is democracy between the leading groups and the groups that are led”.[N.b. All footnotes in Cospito’s contribution are editorial additions; other editorial additions in the text are given in square brackets, whereas curly brackets are used to indicate the author’s textual abbreviations.]